ANALISIS PENGGUNAAN YOUTUBE SEBAGAI MEDIA PEMBELAJARAN BAHASA INDONESIA DALAM KETERAMPILAN MENYIMAK BAGI SISWA KELAS IV SEKOLAH DASAR NEGERI SIDOREJO 02 - Christia Monika; Meidawati Suswandari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study explains the use of YouTube as a tool for learning Indonesian, specifically in the listening skills of fourth-grade students at SD Negeri Sidorejo 02. The main objectives include an analysis of YouTube's role in understanding listening materials such as intonation, expression, language structure, as well as encouraging student motivation and participation. A descriptive qualitative approach was applied with 13 students and a teacher as participants. Data collection included observation, semi-structured interviews, and documentation, then processed using the Miles and Huberman interactive model. The findings revealed that YouTube strengthens students' concentration, mastery of main ideas, detailed information, vocabulary, intonation, and the ability to summarize video content in a structured and relevant manner.